Visible, yet vulnerable: psychodynamic psychotherapy trainees’ experiences of video review in supervision - Orth, Maximilian; Stölting, Julia; Löw, Christina Alexandra; Dinger, Ulrike; Cranz, Anna; Schauenburg, Henning; Nikendei, Christoph (Psychoanalytic psychology, 2026)
The use of video review (VR) in clinical supervision is recommended by psychodynamically oriented scholars and practitioners alike, but little is known about how psychodynamic psychotherapy trainees subjectively experience VR. Thus, the purpose of this study was to illuminate psychotherapy trainees’ perceptions of VR in psychodynamic supervision and the way in which VR subjectively impacts the supervisory alliance as well as trainees’ competency development. A qualitative interview study was conducted with N = 14 psychotherapy trainees from a psychodynamic training institute in Germany. Semistructured interviews with trainees were audio recorded, verbatim transcribed, and analyzed using qualitative content analysis. Results indicate that VR influences the perceived supervision process with regard to content, structure, and the supervisory alliance. Psychodynamic trainees described that by engaging in VR, they honed core psychodynamic skills. This process was embedded in an inherent conflictual theme of VR usage: increased visibility of the therapeutic self and the related shame proneness, but also the courage to reveal oneself via VR and the potential to deepen the supervisory work. We offer a self-psychological perspective on these findings, proposing that trainee selfobject needs for mirroring may become more salient through VR. Results attest to an attunement of psychodynamic psychotherapy trainees to the changes and benefits that VR introduces to psychodynamic supervision.
Gesehen am 16.02.2026